DARI KONSEP KE PANGGUNG : PENDEKATAN PRODUKSI DAN MANAJEMEN PERTUNJUKAN SENI MUSIK DAN SENI TARI DALAM DRAMA MUSIKAL MAHASISWA PRODI PGSD UNIVERSITAS FLORES - Virgilius Bate Lina; Yohana Eufrosina Londa; Maria Ignes Owa; Aldofantino Manuel Lendong (STKIP Subang, 2025)
This study aims to analyze the implementation of arts performance as an outcome of Music Education course in PGSD students. This study uses a qualitative approach with a case study method to observe and analyze the arts performance as an implementation of Music Education course learning. The subjects of this study are PGSD students in semester VI, classes B, D, and E. Data were collected through observation and documentation. The results show that the implementation of arts performance at the end of the semester as a practical exam for Music Education course has a positive impact on students' creativity and confidence. This arts performance is expected to equip PGSD students to showcase their musical talents and play musical instruments when teaching at elementary school. The purpose of this study is to discuss the importance of introducing musical drama in elementary school as an effective method to build creativity and artistic expression.